2022
DOI: 10.1080/21655979.2022.2062969
|View full text |Cite
|
Sign up to set email alerts
|

Galangin alleviates rheumatoid arthritis in rats by downregulating the phosphatidylinositol 3-kinase/protein kinase B signaling pathway

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease that greatly affect patients’ quality of life. Galangin extract is renowned for its anti-proliferative and anti-oxidative characteristics. However, galangin cytotoxicity studies are presently inadequate. We aimed to investigate the therapeutic potential of galangin on RA by investigating the PI3K/AKT signaling pathway.Fibroblast-like synovial cells (FLSs) were exposed to lipopolysaccharide (LPS) to establish an RA model in vitro .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…8 In terms of mechanisms, galangin has reversed liver fibrosis by inhibiting the activation of the PI3K/AKT signaling pathway; 4 galangin has also alleviated rheumatoid arthritis by inhibiting the activation of the PI3K/AKT signaling pathway. 9 The PI3K/AKT signaling pathway plays an important role in the process of neointimal hyperplasia after vascular injury. 10,11 Therefore, it is speculated that galangin has potential regulatory effects on neointima hyperplasia.…”
Section: Introductionmentioning
confidence: 99%
“…8 In terms of mechanisms, galangin has reversed liver fibrosis by inhibiting the activation of the PI3K/AKT signaling pathway; 4 galangin has also alleviated rheumatoid arthritis by inhibiting the activation of the PI3K/AKT signaling pathway. 9 The PI3K/AKT signaling pathway plays an important role in the process of neointimal hyperplasia after vascular injury. 10,11 Therefore, it is speculated that galangin has potential regulatory effects on neointima hyperplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Recent relevant studies reported that inactivation of the PI3K/Akt/mTOR signaling pathway enhanced autophagy, inhibited the proliferation and inflammatory response of synovial cells, and thus alleviated local symptoms of RA [ 39 ]. In addition, studies have also shown that galangin inhibited the development of RA through the PI3K/AKT signaling pathway, which also revealed a new mechanism which might be a feasible method for the treatment of RA [ 40 ]. Recent studies showed that BAI not only inhibited nasopharyngeal carcinoma (NPC) cells proliferation and induced NPC cells apoptosis but also blocked the PI3K/AKT and p53 signaling pathways in CNE2 cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…GAL caused apoptosis in FLSs, reduced cell growth, and promoted cell invasion. GAL inhibited the inflammatory response by lowering IL‐1β, TNF‐α, and IL‐6 levels and suppressing PI3K/AKT signal (X. Deng et al, 2022). Therefore, GAL may be a promising therapy for RA in the future.…”
Section: Anti‐inflammatory Effect Of Galmentioning
confidence: 99%